Low-temperature magnetism and heat transport properties of Ho1-xYxFeO3 (x = 0, 0.2, 0.4) orthoferrite single crystals. Issue 5 (1st April 2020) - Li, Rui; Cao, Chunbin; Jiang, Min
Abstract: Ho1 -x Y x FeO3 ( x  = 0, 0.2, 0.4) single crystals were prepared using a flux method. The Low-temperature magnetism and heat transport properties were then studied. With increasing Y 3+ content, the spin transition of the Fe 3+ ions gradually shifted to a low temperature and the antiferromagnetic ordering of Ho 3+ ions wore off. At T  = 2 K, with the increase of magnetic field, the susceptibility of the samples increased linearly for H // c direction. But they shows more and more obvious twists at lower magnetic fields, with an increase in the doping amount x for H // b direction. At H  = 0 T, with the increase of doping x, the phonon peak of the samples near 17 K decreased rapidly, with the shoulder shape at 1–2 K simultaneously decreasing. The low- T κ ( H ) isotherms of Ho1- x Y x FeO3 single crystal increased along with the increasing magnetic field in general, and the twist of κ ( H ) at 1 T did not change with the magnetic field. However, the twist at 2.5 T changed dramatically with an increased magnetic field and a change in the doping amount x .